2018
DOI: 10.7150/jca.26623
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Changes in the Expression TAZ are Associated with Normal Cervix and Human Cervical Cancer

Abstract: The transcriptional coactivator with the PDZ-binding motif (TAZ) has been associated with different types of cancer. In this study, we examined the TAZ protein expression and cellular localization in 194 cases of human cervical squamous cell carcinoma (SCC). We observed that a normal cervix is characterized by higher expression levels of both nuclear and cytosolic TAZ compared to cervical SCC. Lower membranous and cytosolic TAZ expression levels are associated with lymph node involvement. We observed that TAZ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…In addition, the regulatory factor Yes-associated protein (YAP) and the transcriptional coactivator with PDZ-binding motif (TAZ) can also be activated by LPA4/LPA6 via the Gα12/Gα13 signaling pathway [35]. YAP and TAZ can accelerate the progression of cancer by promoting the proliferation and migration of cancer cells, such as accelerating liver cancer, bladder cancer and lung cancer [36][37][38]. Also, the volume, number and thickness of trabeculae increased in adult LPA4 -/mice, contrary to those observed in LPA 1 -/mice, suggesting that LPA 4 has a negative regulatory effect on bone formation and can counteract LPA 1 -induced bone formation [39].…”
Section: Lpar4mentioning
confidence: 99%
“…In addition, the regulatory factor Yes-associated protein (YAP) and the transcriptional coactivator with PDZ-binding motif (TAZ) can also be activated by LPA4/LPA6 via the Gα12/Gα13 signaling pathway [35]. YAP and TAZ can accelerate the progression of cancer by promoting the proliferation and migration of cancer cells, such as accelerating liver cancer, bladder cancer and lung cancer [36][37][38]. Also, the volume, number and thickness of trabeculae increased in adult LPA4 -/mice, contrary to those observed in LPA 1 -/mice, suggesting that LPA 4 has a negative regulatory effect on bone formation and can counteract LPA 1 -induced bone formation [39].…”
Section: Lpar4mentioning
confidence: 99%
“…A small number of previous studies have analysed the role of TAZ in cervical cancer; however, their findings are controversial. One study identified that TAZ expression is decreased in cervical cancer compared with normal tissue 17 . In contrast, others suggest that TAZ is oncogenic and regulates proliferation, invasion and apoptosis whilst also upregulating PD-L1, a prominent regulator of T-cell evasion 18 .…”
Section: Introductionmentioning
confidence: 99%